Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.0030
|View full text |Cite
|
Sign up to set email alerts
|

α-ω effect and recurrent changes of galactic cosmic rays intensity

Abstract: We recognize a quasi-recurrence with duration of 3 to 4 Carrington rotations period (3-4 CRP) in changes of amplitudes of the 27-day variation of galactic cosmic rays (GCR) intensity, solar activity (SA) and solar wind (SW) parameters, as well. We attribute this phenomenon to the presence of a spatial topological structure (STS) of the solar magnetic field. STS is created by α-ω effect in the inner solar atmosphere, from photosphere to lower corona. STS exists due to the asymmetry of solar dynamo and solar dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Figure 1 illustrates the dominant 11-yr cycle in A 27 and A 14 with maxima around solar maxima and minima around solar minima (Meyer & Simpson 1954). However, in addition to this 11-yr cycle, there is a systematic 22-yr variation in the level of both amplitudes around solar minima, verifying the above-discussed polarity dependence (Richardson et al 1999;Gil & Alania 2001). The amplitudes of the two harmonics of the GCR intensity variation are larger during each positive-polarity minimum than the corresponding amplitudes during the previous or the following negative-polarity minima.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Figure 1 illustrates the dominant 11-yr cycle in A 27 and A 14 with maxima around solar maxima and minima around solar minima (Meyer & Simpson 1954). However, in addition to this 11-yr cycle, there is a systematic 22-yr variation in the level of both amplitudes around solar minima, verifying the above-discussed polarity dependence (Richardson et al 1999;Gil & Alania 2001). The amplitudes of the two harmonics of the GCR intensity variation are larger during each positive-polarity minimum than the corresponding amplitudes during the previous or the following negative-polarity minima.…”
Section: Resultssupporting
confidence: 62%
“…The Hale cycle consists of two successive 11-yr solar activity cycles (also called Schwabe cycles) of opposite magnetic field polarities (Hale et al 1919). Alania and coauthors Gil & Alania 2001) confirmed that the 27-day amplitude of GCR variation is larger during positivepolarity minima (A > 0, magnetic field lines directed outward from the northern pole) than negative (A < 0, magnetic field lines directed outward from the southern pole), in contradiction to the expectation (e.g., Kota & Jokipii 1991) that the 27-day variation is the same for both polarities. Kota & Jokipii (2001) used a non-stationary threedimensional model of GCR transport that included a southwardshifted heliospheric current sheet and corotating interaction regions (CIRs) to demonstrate the polarity dependence of rotation-related quasi-periodic variations of GCR intensity.…”
Section: Introductionmentioning
confidence: 84%
“…The 27-day variations due to solar rotation were shown to have an amplitude that varies with the 11-year and 22-year cycles [24]. There was a report of a possible periodicity with a period of 3-4 solar rotations, which could be attributed to differential rotation of the Sun [23]. Diffusion of cosmic rays in the heliosphere was discussed in the context of ground-based muon observations by GRAPES-3 [8].…”
Section: Pos(icrc2017)1113mentioning
confidence: 99%